Aluminum metal matrix composites reinforced with rice husk ash: A review. (2022) - Dixit, Priyank; Suhane, Amit
Graphical abstract: Abstract: Environmental pollution produced due to the burning of agricultural waste causes serious health problems. An alternative mode of disposition of agricultural waste is a major challenge in the current scenario. Simultaneously development of environmentally friendly and cost-effective composites to be used in various engineering applications is the need of the present century. The usage of agricultural waste in the manufacturing of the composite is a possible solution to both issues. In composite material, tailorable properties of the material are obtained to meet a specific requirement. Researchers have observed that the usage of rice husk ash (RHA) as reinforcement in aluminum and its alloy matrix provides better mechanical properties and tribological behavior to developed composites. Aluminum is lighter than the standard materials used in automotive applications. But its unsatisfactory tribological properties limit its use in the manufacturing of tribomechanical components. Countermeasure for this problem is aluminum metal matrix composites (AMMC) but there is a need for a cheaper reinforcement rather than the commonly used reinforcements like SiC, Al2 O3, TiC, etc. So that cost of the product can be reduced. This article gives a concise overview of the way RHA can be used as an effective and cheapest reinforcement for the development of AMMC and its effect on the mechanical, tribological, and corrosion behavior of developed composites.